2016
DOI: 10.21475/ajcs.2016.10.09.p7747
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability in elephant grass (Pennisetum purpureum Schum.) for energy biomass production

Abstract: The objective of this study was to estimate and evaluate the general and specific combining abilities of hybrid combinations for energy biomass production, adopting the methodology of Griffing as adapted by Geraldi and Miranda Filho in evaluation cuts referring to two periods, the wet and dry seasons, and in relation to total dry matter yield (TDMY). The experiment was conducted at Pesagro Rio, located in Campos dos Goytacazes, RJ, Brazil, in a randomized block design with three replicates. Crosses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Considering the significant lack of rainfall during the second year of evaluation, the results obtained were quite positive. As stated by Menezes et al [9], in elephant grass hybrids, the highest dry matter yield found among hybrids was 19,76 t. ha -1 in water cut. Morais et al [22], examined five genotypes for yield and found a higher mean yield of 23,6 t. ha -1 for the 'Gramafante' cultivar in a cut interval of nine months, which led to lower results than the ones found in this study.…”
Section: Dry Matter Yieldmentioning
confidence: 53%
See 1 more Smart Citation
“…Considering the significant lack of rainfall during the second year of evaluation, the results obtained were quite positive. As stated by Menezes et al [9], in elephant grass hybrids, the highest dry matter yield found among hybrids was 19,76 t. ha -1 in water cut. Morais et al [22], examined five genotypes for yield and found a higher mean yield of 23,6 t. ha -1 for the 'Gramafante' cultivar in a cut interval of nine months, which led to lower results than the ones found in this study.…”
Section: Dry Matter Yieldmentioning
confidence: 53%
“…Studying yield traits in elephant grass with the aim of increasing crop yield is of major importance for the success of breeding programs [8]. Considering that hybridization is one of the best strategies to obtain superior individuals, it is possible to obtain high yielding elephant grass hybrids better than their genitors [9]. Therefore, the scope of this study was to determine the performance per se of elephant grass hybrids obtained for biomass production.…”
Section: Introductionmentioning
confidence: 99%